1990
DOI: 10.1111/j.1095-8649.1990.tb03555.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of grass carp on habitat structure and its subsequent effect on the diet of tench

Abstract: Ecological studies were carried out in shallow experimental sites in the Lancaster Canal to evaluate potential interactions between grass carp and feeding habits of tench.Grass carp. through moderate weed consumption, produced better conditions for the exploitation of benthic organisms by the benthophagous tench. because tench (>35 cm fork length) were able to search for food in the open areas created. This also enabled the fish to make use of zooplankton, mainly the large species Eurycercus laniellarus whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Zooplankton constituted most of the diet of Main Lake tench, but the macro-invertebrate fauna in this lake was very limited in diversity and was dominated by chironomid larvae, oligochaetes and bivalves (Giles et al, 1989). Petridis (1990) found adult tench eating zooplankton and also Asellus and chironomids in shallow experimental sites in the Lancaster canal.…”
Section: Discussionmentioning
confidence: 87%
“…Zooplankton constituted most of the diet of Main Lake tench, but the macro-invertebrate fauna in this lake was very limited in diversity and was dominated by chironomid larvae, oligochaetes and bivalves (Giles et al, 1989). Petridis (1990) found adult tench eating zooplankton and also Asellus and chironomids in shallow experimental sites in the Lancaster canal.…”
Section: Discussionmentioning
confidence: 87%
“…However, the utility of Zn in paleodiet studies has been challenged because of the influence of other factors in an aquatic environment (salinity, thermal regime, pH, alkalinity and the amount of particulate matter in the water) and because the physiological model explaining its trophic performance is not yet fully understood (Ezzo 1994;Halden et al 2000;Trancho and Robledo 2003). The considerably higher content of Zn in more herbivorous common carp and amur (grass carp) than in more omnivorous consuming tench (Petridis 1990;Brönmark 1994;Adámek et al 2003) may indicate another explanation, i.e. that this reversed Eltonian pyramide of Zn can be connected with the high Zn content in plants.…”
Section: Heavy Metalsmentioning
confidence: 92%
“…He also found that fish bigger than 10 cm consumed amphipods and insect larvae. Petridis (1990) observed abundant chironomids and gastropods in alimentary tract of tench in Lancester Canal. However, positive selection of an Isopod Asellus aquaticus whereas negative selection of chironomids.…”
Section: Discussionmentioning
confidence: 99%